Low Dose Oxybutin in Primary Hyperhydrosis: A Prospective Study from a Tertiary Care Center in Nepal - Eliz Aryal; Prashanna Raj Shrestha; Sujan Gautam (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Hyperhydrosis is a clinical condition where  there is excessive sweating beyond the physiological need of the patient’s body. This can  directly or indirectly affect the quality of patients life. Oxybutin is widely used in urology as anticholinergic medication for bladder urge incontinence. It can be used safely at a high doses (over 15 mg/day) to treat urological disorder. It also acts against excessive sweating and can be used in cases of hyperhidrosis.